Electric writing and its retention behavior in ferroelectric 0.94(Bi0.5Na0.5)TiO3-0.06BaTiO3 thin films investigated by piezoelectric force microscopy. (8th August 2016) - Zhan, K.; Su, M.; Zhao, B.; Han, H.; Yuan, Q.; Wang, X. Y.
ABSTRACT: 0.94(Bi0.5 Na0.5 )TiO3 -0.06BaTiO3 (BNT-BT6) thin films with high piezoelectric property have been prepared by metal organic deposition method. The electric writing and its retention behavior of the thin films are investigated. It has been found that electric writing can be done on BNT-BT6 thin films, and the retention behavior of the thin films on Pt electrodes is polarization dependent. The c − domains exhibits better stability than that of c + domains. With the retention time prolongs, the polarized domain states decays. The retention behavior of BNT-BT6 ferroelectric thin film is attributed to the built-in bias at the BNT-BT6/Pt interface, which triggers the nuclei of c − domains near the domain boundary.